Enchytraeus albidus (Enchytraeidae): A test organism in a standardised avoidance test? Effects of different chemical substances - Amorim, Mónica J. B.
Enchytraeids (Enchytraeus albidus) directly improve the pore structure of the soil and are indirectly involved in regulating the degradation of organic matter. Due to their behavior they are able to avoid unfavorable environmental conditions. Avoidance tests allow a first assessment of toxicity of a contaminated or spiked soil within 48 h, by using the reaction of the enchytraeids as measurement endpoint. In this period, the organisms can choose between the control soil and the test soil. In the tests reported here, enchytraeids were exposed to LUFA 2.2 soil spiked with the following set of toxic substances: copper chloride, zinc chloride, cadmium chloride, phenmedipham, benomyl, carbendazim, dimethoate, atrazine, pentachlorophenol, chlorpyriphos, lindane, TBTO, Linear Alkylbenzene Sulfonates (LAS) and boric acid. Different chemical concentrations were tested. EC(50)s ranged from 8 mg/kg (Carbendazim) to > 1000 mg/kg (e.g. LAS). While the tested heavy metals showed clear dose-response relationships, the effect pattern differed considerably in the tests with organic chemicals, e.g. no avoidance behaviour was observed in LAS, even at very high doses. Here we proposed to standardize the Enchytraeid avoidance test in a way similar to what is currently done for the earthworm and collembolan avoidance tests by the International Standardisation Organisation (ISO). (C) 2007 Elsevier Ltd. All rights reserved.